Auditoria e gestão : um estudo de caso dos trabalhos auditoriais realizados no IFES - Silva Neto, Abdo Dias da (2014)
Through this work, it was possible to detect the accumulation of recommendations, which could possibly indicate the presence of failures in management. Thus the aim of this study is to investigate the causes and proposing solutions that contribute to the fulfillment of outstanding recommendations and the improvement of administrative decision-making. Was taken as support the Audit Report Annual Accounts No. 201305863 and form presented tools that assist the management in the management process of decision making. The research universe consists of managers of IFES that live the bureaucratic routine of this educational institution, which enables a perception of inter-professional relationships with the AUDIN (Internal Audit). Data collection was done through a questionnaire, focused on managers' perception of how auditing is conducted in IFES and, parallel, gather information able to equip AUDIN with the tools capable to assist in administrative advice. The research suggests that Internal Audit and managers incorporate different kinds of knowledge to obtain a better performance compared to the demands of Internal and External Control. Over the years, the followup audits of the management of IFES target to act in real time over the actions of management and the potential positive and negative effects. A significant accumulation of recommendations, which indicates the presence of possible failures in the management of this institute was observed. Therefore, the survey showed results that put the Internal Audit at the margin of the management process of IFES